Freedom of Expression and Human Rights Violations under Authoritarian Rule - Tran Ngoc, Nguyen; Vongphachanh, Soutchai; Ha-Duong, Dai; Ratsavong, Somphouthone; Daosavanh, Douangboubpha; Sanamxay, Soulivanh; Ratsavong, Latsanyphone (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2025)
This study examines the mechanisms through which the Lao People’s Democratic Republic restricts freedom of expression and evaluates the effectiveness of international responses to such violations. Despite constitutional guarantees, the Lao government utilizes a range of legal and institutional tools including vague penal codes, media censorship, and digital surveillance, to silence dissent and suppress public discourse. The enforced disappearance of Sombath Somphone serves as a symbolic case of state repression and illustrates the broader chilling effect on civil society. Using a descriptive qualitative method, this study analyzes secondary sources such as human rights reports, international legal instruments, and press freedom indexes. Content analysis was employed to synthesize findings into four key thematic areas: legal-media control, digital repression, enforced disappearance, and international inaction. Data from Freedom House and Reporters Without Borders provided quantitative indicators to support the qualitative insights. The results indicate that repression in Laos is structurally embedded and politically intentional, while international responses remain largely rhetorical and ineffective. The study highlights the limits of ASEAN’s human rights architecture and the enabling role of strategic alliances, particularly with China. Future research should explore regional patterns of digital authoritarianism and the role of transnational civil society in confronting impunity.